Tracing Racism towardsthe Blacks onTHE HELP (2011): A Critical Discourse Analysis - Masriatus Sholikhah (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
Social problem is a social condition that harms people in a society. One of socialproblem that still exist in this world is racism. One of the films that deal with racism is TheHelp film. There are two statements of the problem in this present research; (1) whatare the types of racism found in The Help film, and (2) how do the black people resist racism in The Help film. Furthermore, to answer the first research question particularly used racism theory by Ruth Wodak (2001) and to answer the second research question in which the ways of black people resist racism, the researchers conducted resistance theory by James Scott (1990). The researchers employed Critical Discourse Analysis as the approach. In addition, the researchers employed qualitative research design. Then, in analyzing the data the researchers organized, coded, described and interpreted the data based on the context and the situation. In the findings, the researcher analyzed the data in some quotation from the script. Furthermore, the researchers concluded that the most dominant type of racism is everyday racism. However, for the hidden transcript and public transcript types of resistance, it only found the hidden transcript in the film.